towards a new science, from the onto-epistemical thought of Morín and Martínez Miguelez (Revista Electrónica REDINE, 2019)
Redefining classical science is shown as a necessity in this postmodern era, which is why the following essay intends to analyze from the onto-epistemic point of view the emergence of a new vision of scientific knowledge, from the criteria of recognized authors such as Edgar Morín and Miguel Martinez. The fragmentation of knowledge, the rejection of the subject and the absolute truth are some of the elements most questioned by these theorists, who propose a new direction that points towards a systemic posture, transdisciplinarity and self-reflection of the knowledge that is being generated; all this in order to guarantee our permanence on the planet and respond to current paradigmatic needs.